2019
DOI: 10.1016/j.ebiom.2019.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Human gingival tissue-derived MSC suppress osteoclastogenesis and bone erosion via CD39-adenosine signal pathway in autoimmune arthritis

Abstract: Background Bone destruction is one of many severe complications that occurs in patients with rheumatoid arthritis (RA) and current therapies are unable to cure this manifestation. This study here aims to determine whether GMSC can directly inhibit osteoclast formation and eventually attenuate osteoclastogenesis and bone erosion in an inflammatory milieu. Method GMSC were co-cultured with osteoclast precursors with or without CD39 inhibitor, CD73 inhibitor or adenosine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 43 publications
3
77
0
1
Order By: Relevance
“…The role of macrophages in RA joints is usually attributed to the correlation of macrophage numbers with radiological lesions but this is reinforced by the beneficial effect of targeting macrophages and the mediators they secrete 34,35 . In addition, macrophages differentiate into osteoclasts, resulting in bone destruction 36 . As reported previously, NR1D1 modulated macrophage polarization and SR9009 inhibited osteoclastogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The role of macrophages in RA joints is usually attributed to the correlation of macrophage numbers with radiological lesions but this is reinforced by the beneficial effect of targeting macrophages and the mediators they secrete 34,35 . In addition, macrophages differentiate into osteoclasts, resulting in bone destruction 36 . As reported previously, NR1D1 modulated macrophage polarization and SR9009 inhibited osteoclastogenesis 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we and others have previously reported that CD39 regulates the immunosuppressive function of mesenchymal stem cells. 30 , 47 , 48 , 49 It is reasonable to make a hypothesis that CD39 may be a specific marker for CD8+CD103+ iTregs, which may also play an important role in the immunosuppressive function of CD8+CD103+ iTregs. CD39 and CD73 degrade extracellular ATP to adenosine together.…”
Section: Discussionmentioning
confidence: 99%
“…Entpd1 is responsible for coding CD39, which has a major impact on the equilibrium of ATP and adenosine. 30 , 31 We therefore hypothesized that CD39 plays a functional role in CD8+CD103+ iTregs.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the therapeutic potential of GMSCs have been also demonstrated in RA and other bone erosion related diseases; indeed, systemic infusion of GMSCs can significantly reduce the severity of experimental RA, and restore the balance of Th cell subsets via Fas ligand (FasL) and IL-10 secretion [175]. Transplantation of GMSCs into collagen-Induced arthritis (CIA) mice significantly attenuated the severity of arthritis and osteoclast activity, which in turn reduced bone erosion in vivo via anti-inflammatory CD39-CD73-adenosine signaling pathway [176].…”
Section: Rheumatoid Arthritis (Ra)mentioning
confidence: 99%